Surgical treatment of familial adenomatous polyposis (FAP) of the colon on children. - M.U. Ismayilov; R. Sh. Polukhov; I.V. Poddubny (Pediatric Anesthesia and Critical Care Journal, 2024)
The article analyzed the anamnesis of 46 children treated for familial adenomatous polyposis of the large intestine from 2010 to 2022 (12-year period) in pediatric surgery departments. The presented work is a cohort retrospective scientific-research work, the main indicators of which have been completed since 2010 with a prospective examination. Surgical treatment for confirmed familial adenomatous polyposis of the large intestine was carried out in a planned manner, but before that, preoperative diagnosis, confirmation, and observation with control examinations were carried out for a long time. In all cases, the scope of the operation was completed with total proctocolectomy, ileoanal anastomosis (with or without a protective stoma). Analyzing our experience of treating 46 children with FAP using laparoscopic (in 34 patients) and "open" methods (in 12 children), we believe that the technique of laparoscopic total proctocolectomy developed and applied in our clinic and performed with direct ileoanal anastomosis is effective in this serious disease. is an effective treatment method. Universality, convenience, radicality, etc. it does not lag behind "open" operations in any aspect. Such laparoscopic operations on the large intestine can be carried out in clinics with sufficient experience in that field, with all the necessary equipment, instruments, devices and consumables, as well as with the participation of specialists in related specialties who are usually engaged in the monitoring and treatment of such diseases.